Social Capital, Perceptions and Economic Performance - Hernández, José A.; Guerrero-Luchtenberg, César (Scientific Research, 2016)
This paper describes how social capital emerges, relates to economic performance and evolves in the long run. Using the concept of psychological equilibrium, two types of individuals are generated in the population regarding their willingness to cooperate. We propose an evolutionary (learning) process over those types driven by the total payoffs of the psychological game, and provide a complete description of its dynamics. Macro-perceptions, defined as the individual perception of how cooperative the society is as a whole, are key to explain convergence to the full social capital state in the long run.
Keywords: Psychological Equilibrium; Belief-Dependent Behavior; Evolutionary Games; Replicator Dynamics; Economic Development